Fragile States, Robust Structures: Illegal Police Protection in Buenos Aires - Matías Dewey
Weakness is a quality frequently ascribed to Latin American states. This diagnosis proves faulty since it is possible to find resistant structures inside those states that perpetuate such weaknesses. This article shows that this is the case in regards to the police force of the province of Buenos Aires. Here, I will demonstrate that the police have specialized in selling a service available to criminals and criminal organizations: illegal protection. With information taken from in-depth interviews and official documents, I will show that this protection – contrary to the views of Charles Tilly and Diego Gambetta – is characterized by a temporary suspension of the rule of law.police, protection, politics, organised crime, Buenos Aires